Effects of Carburizing Process Variables on Mechanical and Chemical Properties of Carburized Mild Steel - A. Oyetunji ,; S.O. Adeosun, (Journal of Basic & Applied Sciences, 2021)
This work evaluates the suitability of using palm kernel shell, animal bone (mammalian bones from cattle) and sea shell (oyster shell) materials as carburizers for case hardening of 0.078%C mild steel. The mild steel sample used in this study sourced from universal steel company, Ikeja Lagos Nigeria was cut into suitable sizes using hacksaw machine for tensile and hardness tests. The carburizing media used were milled into fine powder while Barium trioxo (iv) carbonate (VI) (BaCO3) was used as an energizer in the carburizing process. Three rectangular stainless steel plate boxes were fabricated to accommodate each of the steel samples and carburized. A calculated amount of each carburizer was weighed into each of the stainless steel boxes and 20 wt % of BaC03 was mixed with each of them. Mild steel samples were covered completely in each of the boxes with the mixture of the carburizer and energizer placed in the furnace chamber. The carburizing temperatures varied between 700 - 1100oC while the holding time varied between 1-5 hrs. The boxes and its contents were allowed to cool down to room temperature in the furnace after carburization. All samples were heated to 850oC after been soaked for 30 minutes at this temperature and oil quenched. This was to increase the hardness of the case. Fifteen (15) of these samples were further tempered at 350oC for 2hrs to relieve the stress built up during quenching. Hardness test, tensile strength tests and chemical analysis were carried out on the samples. It was observed that the hardness values of the untempered samples are superior to the tempered ones at carburizing temperatures of 7000C, 8000C and 9000C. On the other hand, the tensile strengths of the tempered samples are higher relative to the untempered samples at carburizing temperatures of 7000C, 10000C and 11000C. The results of the carbon analysis show that palm kernel shell and animal bone are potentially suitable to be used as a carburizing media than the sea shell at high temperatures (above 10000C) with holding time above 1 hr.